(untitled) (Emancipação, 2025)
This research aims to understand how environmental education actions take place among the participants of the agroecology group Econorte, located in the municipality of São José do Norte – RS, Brazil. A qualitative methodological approach was employed, using both primary and secondary data. Based on the investigation, it was observed that the Econorte agroecology group develops environmental education actions grounded in a conception of environment and life considered healthy. This is expressed in the group’s experiences of production, organization, and commercialization, as well as in the exchanges between producers and consumers. It was possible to identify changes in understanding and practices, such as: agroecological consumption within family units; the overcoming of the perception that agroecological production is an exclusively female activity; the expansion of political participation in the municipality; and engagement in the construction of movements with environmental agendas, such as the struggle against the presence of large-scale mining enterprises in the territory.